Grounded Theory Methodology - Muszyński, Marcin (Qualitative Research in Andragogy: Polish Research Experiences, 2026)
The chapter presents the origins of the grounded theory methodology (GTM),shedding light on the roots of this method and the traditions it draws upon. Various versionsof grounded theory developed over the past few decades are discussed. The centralpart of the text focuses on describing the procedures used in GTM. Finally, how thismethodology can be applied in the field of andragogical research is also outlined.